2012
DOI: 10.1371/journal.pone.0046352
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Cryostimulation - Potential Beneficial Treatment for Improving Antioxidant Capacity in Healthy Men - Significance of the Number of Sessions

Abstract: It is claimed that WBC (whole-body cryotherapy) enhances the resistance of the human body, also thanks to the beneficial effect on the antioxidant system. Accordingly, this research aimed to evaluate the effect of a series of whole-body cryostimulations on the level of non-enzymatic antioxidants and the activity of antioxidant enzymes in healthy men. The study was carried out on 30 young and healthy men aged 27.8±6.1 years with average body mass index and peak oxygen consumption (46.34±6.15 ml kg−1 •min−1). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
62
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 46 publications
(61 reference statements)
11
62
1
1
Order By: Relevance
“…It is supposed that the response of the antioxidant system is different during one-off cold exposure than after repeated exposure, as shown in previous studies (Lubkowska et al, 2012(Lubkowska et al, , 2009. We may hypothesise that repeated exposure to cold water results in the adaptation of the antioxidant system to mild oxidative stress.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is supposed that the response of the antioxidant system is different during one-off cold exposure than after repeated exposure, as shown in previous studies (Lubkowska et al, 2012(Lubkowska et al, , 2009. We may hypothesise that repeated exposure to cold water results in the adaptation of the antioxidant system to mild oxidative stress.…”
Section: Discussionmentioning
confidence: 63%
“…However, others (Sutkowy et al, 2014) have found no changes in levels of conjugated dienes after CA. Furthermore, (Lubkowska et al, 2012) decreased GSH concentrations and increased GR activities after repeated WBC have also been observed.…”
Section: Discussionmentioning
confidence: 88%
“…A greater number of procedures (e.g. 20-30) could probably increase the treatment effect as was reported in the literature [14,36].…”
Section: Parametersmentioning
confidence: 72%
“…That is why we would like to emphasize that results presented in this paper contain much more data, and the studies may provide innovative and complementary conclusions. In another study [14], the authors showed that the activity of antioxidant enzymes in healthy men depends on the number of WBC procedures. After 10 sessions (temperature: -130°C, time: 3 min) the Table 4.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation